2005
DOI: 10.1089/jwh.2005.14.434
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture in Obese Women: A Randomized, Controlled Pilot Study

Abstract: In this pilot study, electroacupuncture treatment was more effective than situp exercise or no intervention in reducing BW, BMI, and WC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 18 publications
4
42
0
1
Order By: Relevance
“…For EA the evidence is more positive; the majority of studies suggest that EA induces significantly greater weight loss than sham EA, 18 78 or acupuncture performed at no acupuncture points 85 whereas only one study concluded that EA and exercise resulted in similar reductions in body weight. 77 Effects on obesity-related peptides As already mentioned, obesity is characterised by hyperleptinaemia and leptin resistance.…”
Section: Effect Of Different Types Of Acupuncture On Body Weight Alonementioning
confidence: 99%
“…For EA the evidence is more positive; the majority of studies suggest that EA induces significantly greater weight loss than sham EA, 18 78 or acupuncture performed at no acupuncture points 85 whereas only one study concluded that EA and exercise resulted in similar reductions in body weight. 77 Effects on obesity-related peptides As already mentioned, obesity is characterised by hyperleptinaemia and leptin resistance.…”
Section: Effect Of Different Types Of Acupuncture On Body Weight Alonementioning
confidence: 99%
“…Acupuncture significantly reduces BW, compared to placebo or sham treatment, resulting in improved outcomes for obesity relative to conventional medications. Several lines of evidence suggest that acupuncture at body points or/and ear points results in weight reduction, accompanied by diverse beneficial effects in obesity (Table 2) [14,15,[28][29][30][31][32][33][34][35], such as suppression of appetite [15], reduction in BW, body-mass index (BMI), waist circumference (WC), hip circumference (HC) [14,15,[28][29][30][31][32][33][34][35], regulation of fat metabolism (decreases in total cholesterol, triglyceride, lowdensity lipoprotein (LDL), lipoprotein A and apolipoprotein B levels) [30,34], increase in IgG, insulin, C-peptide levels and decrease in glucose levels of obesity [31,35]. Moreover, the psychological status of obese patients is improved by acupuncture [15], even in a negative report on weight loss [27].…”
Section: Clinical Studies Of Acupuncture In Ir-related Diseasesmentioning
confidence: 99%
“…Among several methods used for acupoints stimulation [7], needling is one of the most common methods, and stimulation can either be manual or electrical (electro acupuncture). Acupuncture has been used in the treatment of several diseases including obesity [8,9] and also immunerelated diseases, such as allergic disorders, autoimmune diseases, and immunodeficiency-syndromes [10,11].…”
Section: Introductionmentioning
confidence: 99%